Confronting the practice of surgery on differentiated thyroid cancer with current guidelines in Germany - Schwab, R.; Wieler, H.; Birtel, S.; Ostwald-Lenz, E.; Kaiser, K. P.; Becker, H. P. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: For the surgical therapy of differentiated thyroid cancer precise guidelines are applied by the German medical societies. In a retrospective multicenter study, we investigated the following issues: Are the current guidelines respected?. Is there a difference concerning the surgical radicalism and the outcome?. Does the perioperative morbidity increase with the higher radicalism of the procedure?. Patients, methods: Data gained from 102 patients from 17 regional referral hospitals who underwent surgery for thyroid cancer and a following radioiodine treatment (mean follow up: 42.7 [24-79] months) were analyzed. At least 71 criterias were analyzed in a SPSS file. Results: 46.1% of carcinomas were incidentally detected during goiter surgery. The thyroid cancer (papillary n = 78; follicular n = 24) occurred in 87% unilateral and in 13% bilateral. Papillary carcinomas <1 cm were detected in 25 cases; in five of these cases (20%) contralateral carcinomas <1 cm were found. There were significant differences concerning the surgical radicalism: a range from hemithyroidectomy to radical thyroidectomy with lateral neck dissection. Analysis of the histopathologic reports revealed that lymph node dissection was not performed according to guidelines in 55% of all patients. The perioperative morbidity was lower in departments with a high case load. The postoperative dysfunction of the recurrent laryngeal nerve (mean: 7.9% total / 4.9% nerves at risk) variated highly, depending on differences in radicalism and hospitals. Up to now these variations in surgical treatment have shown no differences in their outcome and survival rates, when followed by radioiodine therapy. Conclusion: Current surgical regimes did not follow the guidelines in more than 50% of all cases. This low acceptance has to be discussed. The actual discussion about principles of treatment regarding, the socalled papillary microcarcinomas (old term) has to be respected within the current guidelines.
Keywords: Thyroid cancer; guidelines